PEMBERLAKUAN FTZ DI KAWASAN EKONOMI KHUSUS (KEK) BATAM DALAM PENINGKATAN PARIWISATA - Fatimah, Zahara; Simamora , Bangun Paruntungan; Silitonga , Frangky (Puslitabmas Batam Tourism Polytecnic, 2022)
Batam is a very strategic location because it is close to Singapore, so it is the center of the government's attention to devote its thoughts to its economic principles and of course to develop, revive tourism in this strategic sense, where we know tourism has declined drastically since the Corona Virus 2019. This study uses a descriptive type of research, which seeks to describe and analyze the development of Special Economic Zones in Batam after the implementation of the Free Trade Zone. The data analysis technique that has been used is qualitative data analysis techniques. The Special Economic Zone (SEZ) in Batam is an investment hope in Indonesia. Pioneering Special Economic Zones have been the reinstatement of free trade and free ports. Facilities and convenience are factors that will attract investors and investors are expected to come to Indonesia, especially Batam, with all applicable permits and related investment activities. Facilities or incentives provided by laws and regulations to investors, such as privileges such as tax holiday treatment for a certain period of time, suspension or exemption from import duties, including taxes, to regions and the public must also be given special attention. The implementation of the SEZ after the implementation of the Free Trade Area on Batam Island has not been carried out properly because the legal certainty of the SEZ has not been ratified into law by the DPR RI, this is what makes investors doubt that the level of legal certainty in Indonesia is very low because of the ease of regulation. issued can change automatically. We hope that in the future we must have strong principles for the sake of our country's economy.